2022
DOI: 10.1200/po.21.00321
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Shifts of Solid Tumor and Liquid Biopsy Sequencing Concordance in Metastatic Breast Cancer

Abstract: PURPOSE Tissue-based next-generation sequencing (NGS) in metastatic breast cancer (mBC) is limited by the inability to noninvasively track tumor evolution. Cell-free DNA (cfDNA) NGS has made sequential testing feasible; however, the relationship between cfDNA and tissue-based testing in mBC is not well understood. Here, we evaluate concordance between tissue and cfDNA NGS relative to cfDNA sampling frequency in a large, clinically annotated mBC data set. METHODS Tempus LENS was used to analyze deidentified rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…They observed that 77.8% of pathogenic tissue variants were detected in cfDNA, and similarly, 75.7% of pathogenic cfDNA variants were identified in tissue when the tests were conducted within a 7‐day interval. However, these percentages decreased to 50.3% and 51.8%, respectively, when the time gap between tests exceeded 365 days 85 . These findings underscore the potential of ctDNA as a non‐invasive alternative approach, particularly in situations where tissue availability is limited.…”
Section: Integration Of Tissue and Ctdna Testingmentioning
confidence: 79%
See 3 more Smart Citations
“…They observed that 77.8% of pathogenic tissue variants were detected in cfDNA, and similarly, 75.7% of pathogenic cfDNA variants were identified in tissue when the tests were conducted within a 7‐day interval. However, these percentages decreased to 50.3% and 51.8%, respectively, when the time gap between tests exceeded 365 days 85 . These findings underscore the potential of ctDNA as a non‐invasive alternative approach, particularly in situations where tissue availability is limited.…”
Section: Integration Of Tissue and Ctdna Testingmentioning
confidence: 79%
“…However, these percentages decreased to 50.3% and 51.8%, respectively, when the time gap between tests exceeded 365 days. 85 These findings underscore the potential of ctDNA as a non-invasive alternative approach, particularly in situations where tissue availability is limited. Moreover, the study highlights the importance of considering the time interval between tests, as the decrease in concordance over time points out the necessity of timely samplings.…”
Section: Expanding the Molecular Profilingmentioning
confidence: 88%
See 2 more Smart Citations
“…17 The reasons for the observed high, but imperfect concordance, also seen in other cancer types, can be varied. They likely include time between the tissue and liquid biopsies (reflecting tumor evolution, especially in late, heavily treated disease 12,25,73 ), intrapatient heterogeneity more likely to be fully captured in ctDNA than in tissue, 14,25 and a deeper analysis of the specific region of the lesion biopsied in tissue because of higher tumor fraction versus broader, lower tumor fraction analysis in ctDNA.…”
Section: Evidence Synthesis Circulating Tumor Dnamentioning
confidence: 99%